Electroporation of mouse embryonic stem cells with Neon device - I. P. Savchenkova; A. A. Savchenkova (Ветеринария сегодня)
Mouse embryonic stem cells are widely used as a promising material for producing of new cellular systems with desired properties in cellular and molecularbiology, pharmacology, virology, medicine, veterinary medicine and biotechnology. Each type of cells requires different electroporation conditions that are determined experimentally. Therefore, the main goal was to optimize conditions of electroporation with Neon® Transfection System, a new-generation device, by selecting and changing of various parameters (voltage, impulse width and number of impulses) to maximize efficiency of D3 embryonic stem cell line transfection and to maintain cell viability. The following parameters were found to be the most optimal for the said cells: impulse voltage– 1200 V, impulse width – 10 ms, number of impulses – 3. Under given conditions, viability of the cells after electroporation was 91%, and transient transfection efficiency (24 hours after electroporation) assessed based on bacterial β-galactosidase production was 88%. It was shown that with higher cell density any electroporation condition tested yielded higher transfection efficiency ranging between 34 and 88%. It was demonstrated that only 5 out of 12 tested protocols with different parameters could be successfully used for insertion of DNA plasmid carrying lacZ Escherichia coli gene into D3 cell line. Thus, the experiment results show the more optimal conditions can be selected experimentally taking into account available information on electroporation protocols for similar cell types recommended by the device manufacturer. Electroporation of mouse embryonic stem cells with the new-generation device can bean effective method for in vitro insertion of nucleic acids into the cells of interest to the researcher.